Piederības izjūtas attīstība skolēnu labizjūtai veselības un fiziskās aktivitātes jomā pamatizglītības 1.posmā - Baļčūne, Agnese (Latvijas Universitāte, 2024)
Bakalaura darba autore: Agnese Baļčūne. Bakalaura darba nosaukums: Piederības izjūtas attīstība skolēnu labizjūtai veselības un fiziskās aktivitātes jomā, pamatizglītības 1. posmā. Darba mērķis: izpētīt piederības izjūtas attīstību skolēnu labizjūtai veselība un fiziskās aktivitātes mācību jomā pamatizglītības 1.posmā. Galvenie rezultāti: balstoties uz pedagogu aptauju, piederības izjūtas attīstību skolēniem veselība un fiziskās aktivitātes mācību jomā veicina sekojoši faktori - nodarbību veidošana, kas saliedē klases kolektīvu (32%), nodarbības, dalot bērnus komandās (26%) un piederības veicināšana skolai (18%), bet darbības, kas sekmē skolēnos piederības izjūtu veselības un fiziskās aktivitātes mācību jomā, visbiežāk ir sadarbības veicināšana starp skolēniem (36%), kopības izjūtas radīšana nodarbībās (29%) un cieņas vienam pret otru veicināšana (16%). Bakalaura darbs uzrakstīts uz 56 lpp., tas ietver 18 attēlus, 9 tabulas, darbā izmantoti 87 literatūras avoti un pievienoti 4 pielikumi.

Author of the bachelor's thesis: Agnese Balcune. Bachelor thesis title: Development of sense of belonging for the well-being of students in the field of health and physical activity, in the 1st stage of basic education. The purpose of the work: to investigate the development of the sense of belonging to the well-being of students, health and physical activities in the field of study in the 1st stage of basic education. The main results: based on a survey of pedagogues, the following factors contribute to the development of a sense of belonging in students, health and physical activities in the field of study - creating lessons that unite the class collective (32%), lessons by dividing children into teams (26%) and promoting belonging to the school (18%), but actions that promote a sense of belonging in students in the field of health and physical activity in the field of learning, the most common are promoting cooperation between students (36%), creating a sense of community in classes (29%) and promoting mutual respect (16%). The bachelor thesis is written on 56 pages, it includes 18 pictures, 9 tables, 87 literary sources and added 4 appendices.
The development of a sense of belonging for the well-being of students in the field of health and physical activity in the 1st stage of basic education
Keywords: Izglītības zinātnes; Piederības; izjūtas; attīstība; labizjūtai; pamatizglītības 1.posmā